Crafting the future: Enhancing gas separation with nanoarchitectonics of bimetallic Ni–Co-ZIF-67 in polysulfone-based mixed matrix membranes - Dety Oktavia Sulistiono; Badrut Tamam Ibnu Ali; Alvin Rahmad Widyanto; Ratna Ediati; Nurul Widiastuti; Witri Wahyu Lestari; Syafsir Akhlus; Rendy Muhamad Iqbal; Semuel Pati Senda; Hamzah Fansuri (Case Studies in Chemical and Environmental Engineering, 2024)
In response to global clean energy demands, this study develops mixed matrix membranes (MMMs) for gas separation in renewable energy applications. MMMs are produced through phase inversion by employing polysulfone and bimetallic-ZIF (Ni–Co-ZIF-67). Bimetallic-ZIF, formed in-situ by Co and Ni metals in water solvent with triethylamine, enhances gas selectivity. MMMs with 4 wt% bimetallic-ZIF, Co: Ni ratio of 9:1 (4Ni10Z67), exhibit remarkable selectivity: CO2/CH4 (21.19), H2/N2 (1.47), H2/CH4 (44.82), and N2/CH4 (30.40). Strong interactions between bimetallic-ZIF and CO2, facilitated by molecular sieving and Ni–Co sites, contribute to these results.